The ISEA winterschool in sports engineering: 5 years of education and team building experiences - Petrone, N.; Marcolin, G.; Odenwald, S.; Senner, V. (Procedia Engineering, 2016)
Aim of the work is to present the ISEA Winterschool experience, spanning over the last 5 years. From 2011 to 2015, 150 students coming from several countries of the world joined the Winterschool in San Vito di Cadore, Italy, spending five days of intense teaching, testing and analysis activities under the guidance of 11 university professors experts in the field of winter sports. The support of about 25 tutors and the presence of a number of industry representative allowed the community to grow in the knowledge of Wintersports engineering and to build and reinforce friendly collaborations. This fostered the exchange of knowledges, stimulated joint projects and student exchanges over the years, that will last as positive results of the experience.